Postpartum bonding and association with depressive symptoms and prenatal attachment in women with fear of birth - Ingegerd Hildingsson; Christine Rubertsson (BMC Pregnancy and Childbirth, 2022)
Abstract Background Co-morbidity is prevalent in women with fear of birth. Depressive symptoms and lack of prenatal attachment might influence the postpartum bonding between the mother and the new-born. Aim To examine the underlying dimensions of the Postpartum Bonding Questionnaire and to investigate associations between depressive symptoms, prenatal attachment and postpartum bonding in women with fear of birth. Methods A longitudinal study comprising 172 women with fear of birth. Data were collected by questionnaires in mid- and late pregnancy and two months after birth. The Edinburgh Postnatal Depressive Scale, Prenatal Attachment Inventory and Postpartum Bonding Questionnaire were investigated. Results Two factors of the Postpartum Bonding Questionnaire were identified: Factor 1 mirrored caring activities and the women’s perceptions of motherhood, whereas Factor 2 reflected negative feelings towards the baby. The Postpartum Bonding Questionnaire was negatively correlated with the Prenatal Attachment Inventory and positively with The Edinburgh Postnatal Depressive Scale. Women with fear of birth and depressive symptoms both during pregnancy and postpartum showed the highest risk of impaired bonding after birth. Primiparity and being single were also associated with impaired bonding. Conclusion A focus on women’s mental health during pregnancy is necessary in order to avoid the negative effects of impaired bonding on the infant. Depressive symptoms could be concurrent with fear of birth and, therefore, it is important to determine both fear of birth and depressive symptoms in screening procedures during pregnancy. Caregivers who meet women during pregnancy need to acknowledge prenatal attachment and thereby influence adaptation to motherhood.